KARAKTERISASI HIDROSOL KULIT BATANG KAYU MANIS (Cinnamomum burmannii) PADA BERBAGAI VARIASI BUKAAN VALVE DESTILASI UAP SKALA PILOT PLAN - Khasanah, Lia Umi; Utami, Rohula; Kawiji, Kawiji; Manuhara, Godras Jati (Universitas Sebelas Maret (UNS), 2021)
Cinnamon is one of the natural flavor commodities that has not been utilized optimally. One of its derivatives product is essential oil. Essential oils are obtained through the distillation process. The by-product of the distillation process is hydrosol. Hydrosol is an emulsion from essential oil which is bound by water molecules. The hydrosol used in this research was a by-product of processing of cinnamon bark essential oils using Pilot Plan-scale steam distillation. The Pilot Plant-scale steam distillation is using 50 % of destilation tank capacity, with a variety of valve openings (¼, ½, and ¾). The study aimed determine characterization of cinnamon bark hydrosols including total phenol, antioxidant activity of reducing power method, antioxidant activity of radical scavenging (DPPH) method, total flavonoids, and antimicrobial activity against Pseudomonas fluorosence; Aspergillus niger; Bacillus plantarum; Staphylococcus aureus; and E.coli. The results showed that variety of valve openings effected the chemical characteristics of cinnamon bark hydrosols including total phenol, total flavonoids, antioxidant activity (reducing power and DPPH methods). The hydrosols of ¾ valve openings treatment showed antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Pseudomonas fluorescens. All hydrosol samples showed no antimicrobial activity against Aspergillus niger and Lactobacillus plantarum. This hydrosol characterization will be used for further recommendations related to the use of hydrosols in the food.